Teaching Clinical Decision-Making Skills to Undergraduate Nursing Students via Web-based Virtual Patients during the COVID-19 Pandemic: A New Approach to The CyberPatientTM Simulator - Masoumian Hosseini, Toktam; Ahmady, Soleiman; Edelbring, Samuel (Journal of Contemporary Medical Sciences, 2022)
Objective: The aim of this study was to investigate the effects of using a virtual patient simulator on the acquisition of clinical decision-making skills in nursing students during the pandemic COVID -19. Methods: This was a quasi-experimental study with a pretest-posttest design. Following the case-based learning strategy, the educational intervention was designed and implemented in five steps (pre-activities, introduction, scenario briefing, web-based clinical scenarios, presentation and de-briefing). We assessed clinical decision-making skills of nursing students before the intervention, after the intervention, and 1 months later, with Clinical Decision-Making questionnaire. In this study SPSS software version 23.0 was used to analyze the data and significance level was considered P <0.05. Results: Clinical decision-making skills of nursing students was compared before (48/04±12/77) and immediately after training (91/49±7/66) using paired tests, and a statistically significant difference was found (P=0/009). Also, before the intervention, most students were thinking analytically (63/80%) and making clinical decisions, while after the intervention, most students had an analytic-intuitive model of clinical decision-making (63/80%). Conclusions: The study showed that the decision-making skills of nursing students were significantly improved by virtual patient simulations. The educational intervention and simulator used in this study can be integrated into undergraduate nursing student education curricula to help them acquire clinical decision-making skills.